Student Engagement in Blended Mathematics Learning: The Role of Perceived Teaching Performance and Learning Attitudes - Rulida, Leonardo Jr (Journal of Interdisciplinary Perspectives, 2025)
The engagement of college students in mathematics presents significant challenges; nevertheless, it is crucial for effective teaching and learning in higher education, particularly in blended learning environments. This study examined the combined effect of college instructors' perceived teaching performance and students' attitudes in learning on the mathematical engagement of Bachelor of Secondary Education (BSED) mathematics students. Data from 120 students were analyzed using a quantitative, non- experimental design with a predictive correlation approach. The stratified analysis showed strong correlations between the perceived teaching performance of college instructors, students' attitudes in learning, and the student's mathematics engagement. The regression analysis further demonstrated how these factors collectively influence students' engagement in mathematics. In light of these findings, educators and institutions should focus on enhancing instructional quality, fostering positive student attitudes, and creating engaging learning environments to support meaningful mathematics engagement and improved outcomes. Prioritizing faculty development and implementing targeted interventions can strengthen teaching effectiveness and student mindset—critical for sustained engagement and academic success in blended learning settings. These efforts can lead to higher performance, better learning experiences, and long-term student success.